Initial Finding of Material Flow Analysis of Food Waste of Particular Restaurants in Yogyakarta, Indonesia - Budijati, Siti Mahsanah; Setiyawan, Panji Dwi (The Indonesian Institute of Science and Technology Research, 2023)
Food waste is still a significant problem today. The Special Region of Yogyakarta contributes 96 tons of food waste daily, with the City of Yogyakarta being the most significant contributor. Food industry services in DIY experience a rapid increase every year. Meanwhile, restaurants and restaurants are the most important contributors to food waste. Yogyakarta City DLH has carried out food waste management activities such as waste bank activities. However, many business actors still need to cooperate, which has resulted in food waste ending up in landfills. Efforts are required to manage food waste to overcome this problem. So, it is necessary to conduct research on food waste flow analysis in food service businesses in Yogyakarta. This research aims to determine the type and quantity of food waste produced and provide an overview of the management costs that occur in restaurants. This research uses the material flow analysis (MFA) method by identifying material flow processes so that it can explore the quantity and type of food waste that occurs at the pre-kitchen, kitchen and post-kitchen stages using STAN software and Sankeymatic diagrams and providing an overview of the total costs in food waste management in restaurants. Interviews and direct observation of restaurants in the eastern and southern regions of Yogyakarta City collected data. The analysis carried out is the flow, type and quantity of food waste and the costs incurred in managing food waste in restaurants. The research results in 8 restaurants in Yogyakarta City in the eastern and southern regions showed that total food waste was 617,906 grams/week. The most significant percentage of food waste at the pre-kitchen stage is lime peel (34%), at the kitchen stage is oil (86%) and at the post-kitchen stage is fish bones (30%). The total costs of managing restaurant food waste are IDR 18,615,000.00/month. The results of this research can be used to predict the quantity and type of food waste in the future so that it can be used to plan policies to overcome food waste.